Gas-sensing performance of BC3 nanotubes for detecting poisonous cyanogen gas: a periodic DFT approach. (15th June 2021) - Rahimi, Rezvan; Solimannejad, Mohammad
Abstract : An efficient sensor was produced to detect toxic cyanogen gas even in the presence of water, oxygen, and nitrogen molecules due to the significant sensitivity and selectivity of the desired BC3 NTs. Abstract : In this research, the significant sensor properties of BC3 nanotubes (BC3 NTs) for the detection of poisonous cyanogen gas are presented through periodic density functional theory (DFT) calculations. The most stable complex formed between cyanogen and the BC3 NTs exhibited a calculated adsorption energy of −0.763 eV with a recovery time of 0.68 seconds at 298 K. Cyanogen gas is therefore detectable due to the appropriate recovery time under ambient conditions. The uptake of cyanogen gases prompted a substantial change of 27.00% in the band gap ( E g ) of BC3 NTs in the most sensitive complexes. The sensor is efficient because there is significant sensitivity and selectivity of the desired BC3 NTs in detecting toxic cyanogen gas even in the presence of water, oxygen, and nitrogen molecules. The gas-sensing capacity of BC3 nanosheets (BC3 NSs) toward cyanogen gas was also studied and compared with the BC3 NTs. It was shown that BC3 NTs are a more convenient and sensitive sensor as compared to BC3 NSs for the detection of cyanogen in practical applications.